Anthropometric status between tribal and non tribal school children (Faridpur Medical College Journal, 2015)
A descriptive cross sectional study named "Anthropometric status between tribal and non tribal school children" was conducted on Guimara primary school, Matiranga, Kharagrachari and Thana primary school, Sitakund, Chittagong to assess the difference in nutritional status between tribal and non tribal school children aged 6 to 10 years in terms of selected indicators. The indicators were height for age Z score, weight for height Z score, and weight for age Z score. Data were collected by interview from mother of the child through semi-structured questionnaire and measuring height and weight of 128 children. Among them 63 were selected from tribal community and 65 from non tribal area. The study revealed that 9.2% non tribal and 7.9% tribal children were severely stunted, 12.3% non tribal and 1.6% tribal were moderately wasted and 9.2% non tribal and 1.6% tribal children were moderately underweight. In relation to sex among tribal children 12.9% tribal boys and 3.1% tribal girls were severely stunted, only 3.2% tribal boys were both moderately wasted and underweight. In case of non tribal children 17.9% boys and 2.7% girls were severely stunted, 17.9% boys and 8.1% girls were moderately wasted and 17.9% boys and 2.7% girls were moderately underweight. According to the age group of 6 to 7 years it was found that, only 4.2% non tribal children were severely stunted and 29.2% were moderately stunted where as 12% tribal children were moderately stunted. In both case of moderately wasting and underweight non tribal were 8.5% more than tribal children and among 8 to 10 years age group it was 12.2% and 7.3% more respectively and in case of severely stunted tribal children were 1% more than non tribal. Improper dietary practice was also found among the two group of study population. Information and health education should be provided to the parents of the children by community participation regarding proper use of sanitary latrine, provision of safe drinking water and proper dietary practice.Faridpur Med. Coll. J. 2014;9(1): 12-18